Resolving Business Disputes between Micro Small Medium Enterprises with Consumers Through Mediation - Walujo, Christian Rico; Soekorini, Noenik; Astutik, Sri; Cornelis, Vieta Imelda (Law and Economics, 2025)
The aim of this research is to analyze the legal relationship between traders and Micro, Small and Medium Enterprises (MSME) consumers who are in dispute and explore how to resolve MSME business disputes through mediation. This normative juridical research uses a statutory regulatory approach and a conceptual approach. The legal materials used consist of primary law, namely the Civil Code (KUHPer), the Civil Procedure Code (KUHAPer), and Law Number 30 of 1999 concerning Arbitration and Alternative Dispute Resolution. Secondary Law  consists of literature research related to the problem and Tertiary Law consists. The results of this research are that the legal relationship between the parties in an MSME business dispute can be in the form of a sale and purchase agreement, work contract, or compensation agreement between traders, consumers and the causes of MSME business disputes are negligence of contract agreements, negligence of business actors, product quality standards, late delivery, market competition, environmental issues, labor conflicts, changes in government regulations, internal company conflicts, cultural and language differences between regions and also economic turmoil. For MSMEs, mediation is always the main choice for business actors in resolving business disputes because it is simple, fast, low cost and satisfies all parties